'Marsquake' hunter prepares to land on the red planet. (29th November 2018) - Witze, Alexandra
Joint US-French-German mission will monitor seismic activity for clues to Mars's internal structure. Joint US-French-German mission will monitor seismic activity for clues to Mars's internal structure. An artist's impression of the InSight lander on Mars. NASA/JPL-CALTECH